2021
DOI: 10.1038/s41598-020-80673-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between individual chamber and whole shell Mg/Ca ratios in Trilobatus sacculifer and implications for individual foraminifera palaeoceanographic reconstructions

Abstract: Precisely targeted measurements of trace elements using laser ablation inductively coupled plasma mass spectrometry (LA-ICPMS) reveal inter-chamber heterogeneities in specimens of the planktic foraminifer Trilobatus (Globigerinoides) sacculifer. We find that Mg/Ca ratios in the final growth chamber are generally lower compared to previous growth chambers, but final chamber Mg/Ca is elevated in one of thirteen sample intervals. Differences in distributions of Mg/Ca values from separate growth chambers are obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…In Figure 7, we plot δ 18 O and δ 13 C values against median Mg/Ca ratios of all spots per individual which, despite final chamber depletion, is a good representative of past ocean conditions (Fehrenbacher et al., 2020; Rustic et al., 2021). There is no detectable correlation between stable isotopes and Mg/Ca ratios (Figure 7; Table S12–S17 in Supporting Information ) in all subspecies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 7, we plot δ 18 O and δ 13 C values against median Mg/Ca ratios of all spots per individual which, despite final chamber depletion, is a good representative of past ocean conditions (Fehrenbacher et al., 2020; Rustic et al., 2021). There is no detectable correlation between stable isotopes and Mg/Ca ratios (Figure 7; Table S12–S17 in Supporting Information ) in all subspecies.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental design of our study meant that an investigation of intratest and interspecific banding differences, while of fundamental interest, is not possible given the nature of our data collection. Chamber heterogeneity comparisons between test averaged LA‐ICP‐MS and solution ICP‐MS have shown that averaging Mg/Ca across chambers is a good indicator of past ocean conditions (Fehrenbacher et al., 2020; Rustic et al., 2021). We therefore recommend that studies using LA‐ICP‐MS should measure all chambers in the final whorl (Fehrenbacher et al., 2020; Rustic et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we still compared intra‐test variability using first moment statistics for consistency with other studies (e.g., Fehrenbacher & Martin, 2014; Sadekov et al., 2005). Some extant species show significantly higher or lower Mg/Ca in the final chambers of their tests (Rustic et al., 2021; Sadekov et al., 2005, 2008), which means that the time spent in the adult phase and therefore the size of the final chamber may skew test Mg/Ca averages. Our results show that mean chamber Mg/Ca values and standard deviations do vary within the same test, but there is no consistent trend through successive chambers in the direction of growth (Figure S8 in Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
“…Such targeted measurements fundamentally rely on an understanding of how Mg is distributed within the test wall (e.g., Sadekov et al., 2008). For example, the supposed lack of high Mg/Ca bands in the final chambers of Tribolatus sacculifer compared with preceding chambers means that measurements based only on final chambers of this species could be skewed toward lower Mg/Ca values than bulk test averages (Rustic et al., 2021; Sadekov et al., 2005). Furthermore, standard chemical cleaning protocols prior to Mg/Ca analysis (Barker et al., 2003) may result in the preferential dissolution of high Mg/Ca portions of the test, skewing Mg/Ca measurements to different degrees in different species.…”
Section: Introductionmentioning
confidence: 99%